Analisis In Silico Interaksi antara Interferon Beta dengan Senyawa Turunan Flavonoid dan Terpenoid dari Bunga Carthamus tinctorius - Lismayana Hansur; Nurmasita; Paisal; Sandy Vitria Kurniawan (MEDICINUS, 2025)
Background: Kasumba turatea (Carthamus tinctorius) has long been empirically used by the people of South Sulawesi as a traditional medicine for diseases caused by viral infections. This plant is known to contain compounds such as thymol, carvacrol, carthamon, chalcone, and linalool, which have potential immunomodulatory activity, including relevance to multiple sclerosis. One of the immune mechanisms which play a role is interferon beta (IFN-β), whose function is influenced by β-glucan, which can enhance IFN-β expression. Objective: This study aims to explore the interaction between thymol, carvacrol, carthamon, chalcone, and linalool — compounds with immunomodulatory— and IFN-β through acomputational (in silico) approach. Methods: The method used in this study is molecular docking using AutoDock Tools, AutoDock Vina, and Discovery Studio applications. The 3D structure of interferon beta was obtained from the Protein Data Bank (PDB) with PDB ID 1AU1. Beta-D-glucan (BDG) was used as the control compound. The ligands examined included carthamon, carvacrol, chalcone, linalool, and thymol. Results: Docking results showed that carthamon exhibitedthe highest binding affinity among the ligands. Key residues involved in ligand interaction at the active site of IFN-β were glutamic acid 42, arginine 28, serine 13, asparagine 90, and leucine 9, which interacted via hydrogen bonds. Conclusion:This study provides preliminary evidence that active compounds from kasumba turatea, particularly carthamon, have the potential to interact wit IFN-β. These findings can serve as a foundation for further research to examine the interaction of carthamon with IFN-β, which could enhance immunomodulatory capabilities.